2006
DOI: 10.1577/a04-041.1
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Postlarval Macrobrachium rosenbergii at Two Temperatures

Abstract: Postlarvae of the giant Malaysian prawn Macrobrachium rosenbergii were reared for a 120‐d period under laboratory conditions at 20°C and 33°C to calculate survival. Ninety‐six 50‐d‐old postlarvae were stocked in eight 70‐L aquaria. A balanced commercial feed containing 40% protein was supplied daily at 20% to 9% of body weight during the first 2 months and at 5% to 3% of body weight during the final 2 months. Live brine shrimp Artemia franciscana were also provided as a supplemental food (10 organisms/L). Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In general, the prawn's survival was low compared with the results obtained by other research with similar initial age prawns (Balazs & Ross1976, Goda 2008; it could be caused by low temperature on some days of our bioassay. Ortega-Salas & Arana-Magallón (2006) reported that the survival of 50 days old prawns was 81% at 33°C and 67% at 20°C after two months of culture. There were no differences in prawn's survival rate between treatments and control, which is remarkable considering that we used diets with low P and L levels, but biofloc contributed to cover nutrient requirements.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the prawn's survival was low compared with the results obtained by other research with similar initial age prawns (Balazs & Ross1976, Goda 2008; it could be caused by low temperature on some days of our bioassay. Ortega-Salas & Arana-Magallón (2006) reported that the survival of 50 days old prawns was 81% at 33°C and 67% at 20°C after two months of culture. There were no differences in prawn's survival rate between treatments and control, which is remarkable considering that we used diets with low P and L levels, but biofloc contributed to cover nutrient requirements.…”
Section: Discussionmentioning
confidence: 99%